TP53INP1, a tumor suppressor, interacts with LC3 and ATG8-family proteins through the LC3-interacting region (LIR) and promotes autophagy-dependent cell death - Seillier, M. (2012)
TP53INP1 (tumor protein 53-induced nuclear protein 1) is a tumor suppressor, whose expression is downregulated in cancers from different organs. It was described as a p53 target gene involved in cell death, cell-cycle arrest and cellular migration. In this work, we show that TP53INP1 is also able to interact with ATG8-family proteins and to induce autophagy-dependent cell death. In agreement with this finding, we observe that TP53INP1, which is mainly nuclear, relocalizes in autophagosomes during autophagy where it is eventually degraded. TP53INP1-LC3 interaction occurs via a functional LC3-interacting region (LIR). Inactivating mutations of this sequence abolish TP53INP1-LC3 interaction, relocalize TP53INP1 in autophagosomes and decrease TP53INP1 ability to trigger cell death. Interestingly, TP53INP1 binds to ATG8-family proteins with higher affinity than p62, suggesting that it could partially displace p62 from autophagosomes, modifying thereby their composition. Moreover, silencing the expression of autophagy related genes (ATG5 or Beclin-1) or inhibiting caspase activity significantly decreases cell death induced by TP53INP1. These data indicate that cell death observed after TP53INP1-LC3 interaction depends on both autophagy and caspase activity. We conclude that TP53INP1 could act as a tumor suppressor by inducing cell death by caspase-dependent autophagy. © 2012 Macmillan Publishers Limited All rights reserved.